Design of Automatic Switchover System of Mine Ventilators without Blowing-out Based on S7-300 PLC - JIAO Xiao-yu; MA Xiao-ping; ZOU Xiao-fu (Gong-kuang zidonghua, 2011)
In view of problem that high gas outburst mines would appear over-limit phenomenon of gas concentration in short stop time of ventilator when main ventilator makes switchover, the paper proposed a design scheme of automatic switchover system of mine ventilator without blowing-out based on S7-300 PLC. The system uses scheme of installing bypass air door to start standby ventilator, namely starting standby ventilator before main ventilator stops running and through coordination of open degree of main and side air doors to ensure stability of air flow of switchover system of ventilators. The actual application showed that the system can ensure safety in switchover process of ventilators without blowing-out effectively.